2018
DOI: 10.1111/evo.13587
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenecks and inbreeding depression in autotetraploids

Abstract: Inbreeding depression is dependent on the ploidy of populations and can inhibit the evolution of selfing. While polyploids should generally harbor less inbreeding depression than diploids at equilibrium, it has been unclear whether this pattern holds in non-equilibrium conditions following bottlenecks. We use stochastic individual-based simulations to determine the effects of population bottlenecks on inbreeding depression in diploids and autotetraploids, in addition to cases where neo-autotetraploids form fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 78 publications
2
16
1
Order By: Relevance
“…Moreover, contemporary levels of inbreeding depression may not reflect those immediately following bottlenecks, because such declines in inbreeding depression should be erased relatively quickly after populations rebound in size (Kirkpatrick & Jarne ; Balick et al. ; Layman & Busch ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, contemporary levels of inbreeding depression may not reflect those immediately following bottlenecks, because such declines in inbreeding depression should be erased relatively quickly after populations rebound in size (Kirkpatrick & Jarne ; Balick et al. ; Layman & Busch ).…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding depression, which is mainly caused by partially or fully recessive mutations (Charlesworth & Wills 2009), is expected to decline following a population's recovery from a bottleneck when homozygous mutations are purged by natural selection (Kirkpatrick & Jarne 2000;Glemin 2003;Balick et al 2015). This expectation follows from theoretical work in diploid populations (Glemin 2003;Balick et al 2015;Peischl & Excoffier 2015), yet the purging of recessive mutations is less effective in tetraploids (Ronfort 1999;Layman & Busch 2018). Moreover, contemporary levels of inbreeding depression may not reflect those immediately following bottlenecks, because such declines in inbreeding depression should be erased relatively quickly after populations rebound in size (Kirkpatrick & Jarne 2000;Balick et al 2015;Layman & Busch 2018).…”
Section: Ability To Self-fertilizementioning
confidence: 99%
See 1 more Smart Citation
“…For example, an autotetraploid genotype with the "abcd" alleles at a locus that can form six expected combinations of gametes, namely, "ab", "ac", "ad", "bc", "bd", and "cd", but a homozygous gamete can be generated, e.g., "aa", "bb", "cc", or "dd" (Haldane, 1930;Mather, 1935;Haynes and Douches, 1993). How to accommodate DR and its implications in a breeding program as well as the use of these marker loci in linkage mapping has been discussed for a long time (Butruille and Boiteux, 2000;Luo et al, 2000;Xu et al, 2013;Layman and Busch, 2018;Bourke et al, 2019) for some economically important species, such as potato (Bradshaw, 2007;Bourke et al, 2015) and alfalfa (Julier et al, 2003), but has not yet been reported in guinea grass.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an autotetraploid genotype with the 'abcd' alleles at a locus that can form six expected combinations of gametes, namely, 'ab', 'ac', 'ad', 'bc', 'bd', and 'cd', but a homozygous gamete can be generated, e.g., 'aa', 'bb', 'cc', or 'dd' (Haldane, 1930;Mather, 1935;Haynes and Douches, 1993). How to accommodate DR and its implications in a breeding program as well as the use of these marker loci in linkage mapping has been discussed for a long time (Butruille and Boiteux, 2000;Luo et al, 2000;Xu et al, 2013;Layman and Busch, 2018;Bourke et al, 2019) for some economically important species, such as potato (Bradshaw, 2007;Bourke et al, 2015) and alfalfa (Julier et al, 2003), but has not yet been reported in guinea grass.…”
Section: Introductionmentioning
confidence: 99%